Non-aqueous electrolyte, non-aqueous electrolyte secondary battery containing non-aqueous electrolyte, and compound
Patent Information
- Application Number
- JP2023124829
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0009】 本発明によれば、非水系電解液二次電池の初回の充放電後の放電容量、及び初期高温充電保存試験後の残存容量を向上させることを達成し得る非水系電解液を提供できる。また、当該非水系電解液を備えた非水系電解液二次電池を提供できる。
Smart Images

Figure 2025021104000001 
Figure 2025021104000002 
Figure 2025021104000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte, a non-aqueous electrolyte secondary battery containing the non-aqueous electrolyte, and a compound. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries such as lithium secondary batteries are being put to practical use in a wide range of applications, from so-called consumer power sources such as mobile phones and notebook computers to on-board power sources for driving automobiles and the like. However, in recent years, there has been an increasing demand for higher performance for non-aqueous electrolyte secondary batteries, and in particular, there is a demand for improvements in various battery characteristics such as high capacity, low-temperature usage characteristics, high-temperature storage characteristics, cycle characteristics, and safety during overcharging. As a means for improving these characteristics, many technologies have been considered for various battery components, including active materials for positive and negative electrodes and non-aqueous electrolytes.
[0003] For example, Patent Document 1 describes lithium 3-propionitrile trimethylborate, and describes a study on improving cycle performance at high temperature and high voltage. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2016-533624 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the present inventors investigated the method described in the above document, they found that there was a problem in that the discharge capacity after the first charge / discharge and the remaining capacity after a high-temperature storage test were insufficient.
[0006] Therefore, an object of the present invention is to provide a nonaqueous electrolyte, a nonaqueous electrolyte secondary battery, and a compound that improve the discharge capacity after the initial charge / discharge of a nonaqueous electrolyte secondary battery and the remaining capacity after a high-temperature storage test. [Means for solving the problem]
[0007] Means of the Invention In view of the above circumstances, the present inventors conducted intensive research and found that the above object can be achieved by a non-aqueous electrolyte solution containing an anion represented by general formula (1), thereby completing the present invention.
[0008] That is, the gist of the present invention lies in the following. [1] A nonaqueous electrolyte solution containing a nonaqueous solvent and two or more kinds of anions, at least one of which is an anion represented by general formula (1): [ka] (In general formula (1), X is a divalent hydrocarbon group, R is a hydrocarbon group, and n is an integer of 2 or more and 4 or less.) [2] The nonaqueous electrolyte solution according to [1], in which α / β is 0.0001 or more and 0.1 or less, where α is the content (mass%) of the anion represented by general formula (1) and β is the total content (mass%) of anions other than the anion represented by general formula (1). [3] The non-aqueous electrolyte contains PF6 as an anion other than the anion represented by general formula (1). - , BF4 - , ClO4 - , N(FSO2)2 - , N(FSO2)(CF3SO2) - , N(CF3SO2)2 - , N(C2F5SO2)2 - The non-aqueous electrolyte solution according to [1] or [2], comprising at least one selected from the group consisting of fluorooxalatoborate, difluorooxalatoborate, bisoxalatoborate, tetrafluorooxalatophosphate, difluorobisoxalatophosphate, and trisoxalatophosphate. [4] The nonaqueous electrolyte solution according to any one of [1] to [3], further comprising at least one compound selected from the group consisting of saturated cyclic carbonates, chain carbonates, chain carboxylates, cyclic carboxylates, sulfone-based compounds, ether-based compounds, and nitrile-based compounds (limited to those not having an anion represented by general formula (1)). [5] A nonaqueous electrolyte secondary battery comprising the nonaqueous electrolyte according to any one of [1] to [4]. [6] A lithium salt containing an anion represented by general formula (1): [ka] (In general formula (1), X is a divalent hydrocarbon group, R is a hydrocarbon group, and n is an integer of 2 or more and 4 or less.) Effect of the Invention
[0009] According to the present invention, it is possible to provide a nonaqueous electrolyte that can improve the discharge capacity of a nonaqueous electrolyte secondary battery after the first charge / discharge and the remaining capacity after an initial high-temperature charged storage test, and also to provide a nonaqueous electrolyte secondary battery including the nonaqueous electrolyte.
[0010] The present inventors speculate that the reason why the non-aqueous electrolyte having the configuration of the present invention exhibits such excellent effects is as follows. That is, the anion represented by general formula (1) forms a borate-derived coating on the positive electrode, thereby exerting a positive electrode protection effect. The borate salts described in the prior art documents have only one nitrile group in the molecule and therefore have a weak effect on the positive electrode, but the anion represented by general formula (1) has multiple nitrile groups in the molecule and therefore acts strongly on the positive electrode surface, and the borate-derived coating having the ability to protect the positive electrode can remain stably on the positive electrode surface for a long period of time, thereby exhibiting favorable battery performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The following describes in detail the embodiment of the present invention. However, the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the present invention can be modified and implemented as desired without departing from the gist of the present invention.
[0012] [1. Non-aqueous electrolyte] [1-1. Anion represented by general formula (1)] The nonaqueous electrolyte used in the nonaqueous electrolyte secondary battery of the present invention contains an electrolyte and a nonaqueous solvent for dissolving the electrolyte, similar to a general nonaqueous electrolyte. The nonaqueous electrolyte contains two or more kinds of anions, and at least one of the anions contains an anion represented by general formula (1). [ka] In general formula (1), X is a divalent hydrocarbon group, R is a hydrocarbon group, and n is an integer of 2 or more and 4 or less. The number of carbon atoms in the hydrocarbon group X is not particularly limited, but from the viewpoint of efficiently forming a film on the positive electrode, it is usually 10 or less, preferably 6 or less, more preferably 3 or less, and particularly preferably 2 or less. On the other hand, it is usually 1 or more, preferably 2 or more. The number of carbon atoms in the hydrocarbon group R is not particularly limited, but from the viewpoint of efficiently forming a film on the positive electrode, it is usually 10 or less, preferably 6 or less, and more preferably 3 or less. On the other hand, it is usually preferably 1 or more. In terms of efficiently forming a film on the positive electrode, n in the anion represented by general formula (1) is usually 2 or more, preferably 3 or more, and usually 4 or less.
[0013] The term "hydrocarbon group" refers to a group composed of carbon atoms and hydrogen atoms, and is roughly divided into aliphatic hydrocarbon groups and aromatic hydrocarbon groups. The term "aliphatic hydrocarbon group" refers to a non-cyclic or cyclic hydrocarbon group composed of carbon atoms and hydrogen atoms, and does not have an aromatic structure. The term "aromatic hydrocarbon group" refers to a hydrocarbon group having an aromatic structure composed of carbon atoms and hydrogen atoms. Among these, aliphatic hydrocarbon groups are preferred, and non-cyclic hydrocarbon groups are more preferred.
[0014] Specific examples of the hydrocarbon group R include aliphatic hydrocarbon groups such as alkyl groups, alkenyl groups, and alkynyl groups, and aromatic hydrocarbon groups such as aryl groups and aralkyl groups. Among these, from the viewpoint of suppressing side reactions of the anion represented by general formula (1) on the electrode, alkyl groups, alkenyl groups, and alkynyl groups are preferred, alkyl groups and alkenyl groups are more preferred, and alkyl groups are particularly preferred. Examples of the alkyl group include linear alkyl groups, branched alkyl groups, and alkyl groups having a cyclic structure. Of these, linear alkyl groups are preferred. Specific examples of the linear alkyl group include linear alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, and an n-decyl group. Of these, linear alkyl groups having 1 to 6 carbon atoms are preferred, and linear alkyl groups having 1 to 3 carbon atoms are particularly preferred. Specific examples of the branched alkyl group include branched alkyl groups having 1 to 10 carbon atoms, such as a methylethyl group, a methylpropyl group, a methylbutyl group, a methylpentyl group, a methylhexyl group, a methylheptyl group, a methyloctyl group, a methylnonyl group, a tert-butyl group, a dimethylpropyl group, a dimethylbutyl group, a dimethylpentyl group, a dimethylhexyl group, a dimethylheptyl group, a dimethyloctyl group, a trimethylhexyl group, a trimethylheptyl group, an ethylpentyl group, an ethylhexyl group, an ethylheptyl group, an ethyloctyl group, a propylhexyl group, a propylheptyl group, and a butylhexyl group. Among these, branched alkyl groups having 1 to 6 carbon atoms, such as a methylethyl group, a methylpropyl group, a methylbutyl group, a methylpentyl group, a dimethylethyl group (tert-butyl group), a dimethylpropyl group, and a dimethylbutyl group, are preferred, and branched alkyl groups having 1 to 4 carbon atoms, such as a methylethyl group, a methylpropyl group, and a dimethylethyl group (tert-butyl group), are particularly preferred. In the above examples of the branched alkyl group, the branching position is optional. Specific examples of the alkyl group having a cyclic structure include alkyl groups having a cyclic structure having 3 to 10 carbon atoms, such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, a cyclohexylmethyl group, a cyclohexylethyl group, a methylcyclohexyl group, a dimethylcyclohexyl group, an ethylcyclohexyl group, and a methylcyclohexylmethyl group. Of these, alkyl groups having a cyclic structure containing 3 to 8 carbon atoms, such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclocyclohexylmethyl group, a cyclohexylethyl group, a methylcyclohexyl group, a dimethylcyclohexyl group, an ethylcyclohexyl group, and a methylcyclohexylmethyl group, are preferred, and alkyl groups having a cyclic structure containing 6 to 8 carbon atoms, such as a cyclohexyl group, a cyclohexylmethyl group, a cyclohexylethyl group, a methylcyclohexyl group, a dimethylcyclohexyl group, an ethylcyclohexyl group, and a methylcyclohexylmethyl group, are particularly preferred. Among the above-mentioned alkyl groups, alkyl groups having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, a methylethyl group, an n-butyl group, a tert-butyl group, an n-pentyl group, and an n-hexyl group, are preferred, alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, a methylethyl group, an n-butyl group, and a tert-butyl group, are more preferred, a methyl group and an ethyl group are further preferred, and a methyl group is particularly preferred. Specific examples of the alkenyl group include alkenyl groups having 2 to 12 carbon atoms, such as vinyl, allyl, isopropenyl, methallyl, 2-butenyl, 3-methyl-2-butenyl, 3-butenyl, and 4-pentenyl. Among them, preferred are alkenyl groups having 2 to 6 carbon atoms, such as vinyl, allyl, methallyl, and 2-butenyl, more preferred are alkenyl groups having 2 to 4 carbon atoms, such as vinyl, allyl, and methallyl, even more preferred are vinyl and allyl, and particularly preferred is vinyl. The above-mentioned alkenyl groups are preferred because the anion represented by the general formula (1) can suitably form an insulating coating on the surface of the positive electrode active material and / or negative electrode active material, thereby enhancing the effect of the insulating coating. Specific examples of the alkynyl group include alkynyl groups having 2 to 10 carbon atoms, such as ethynyl, 2-propynyl, 2-butynyl, 3-butynyl, 4-pentynyl, and 5-hexynyl. Among these, alkynyl groups having 2 to 6 carbon atoms, such as ethynyl, 2-propynyl, 2-butynyl, and 3-butynyl, are preferred, and ethynyl and 2-propynyl are particularly preferred. The above-mentioned alkynyl groups are preferred because the anion represented by the general formula (1) can suitably form an insulating coating on the surface of the positive electrode active material and / or the negative electrode active material, thereby enhancing the effect of the insulating coating. Specific examples of the aryl group include aryl groups having 6 to 10 carbon atoms, such as a phenyl group, a tolyl group, and a mesityl group. Of these, aryl groups having 6 to 7 carbon atoms, such as a phenyl group and a tolyl group, are preferred, and a phenyl group is particularly preferred. Examples of the aralkyl group include aralkyl groups having 7 to 10 carbon atoms, such as a phenylmethyl group (benzyl group), a phenylethyl group (phenethyl group), a phenylpropyl group, and a phenylbutyl group. Of these, aralkyl groups having 7 to 8 carbon atoms, such as a benzyl group and a phenethyl group, are preferred, and a benzyl group is particularly preferred.
[0015] The divalent hydrocarbon group X is preferably a divalent aliphatic hydrocarbon group. Specific examples of the divalent aliphatic hydrocarbon group include an alkylene group, an alkenylene group, an alkynylene group, etc. Among these, an alkylene group is preferred from the viewpoint of suppressing side reactions of the anion represented by the general formula (1) on the electrode. Specific examples of the alkylene group include alkylene groups having 1 to 10 carbon atoms, such as a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, and a pentamethylene group. Of these, alkylene groups having 1 to 6 carbon atoms, such as a methylene group, an ethylene group, a trimethylene group, and a tetramethylene group, are preferred, and alkylene groups having 1 to 3 carbon atoms, such as a methylene group, an ethylene group, a trimethylene group, and a propylene group, are particularly preferred. Specific examples of the alkenylene group include alkenylene groups having 1 to 10 carbon atoms, such as *-CH=CH-*, *-CH=CH-CH2-*, *-CH=CH-CH2-CH2-*, *-CH2-CH=CH2-CH2-*, and *-CH=CH-CH2-CH2-CH2-*. Among these, alkenylene groups having 1 to 6 carbon atoms, such as *-CH=CH-*, *-CH=CH-CH2-*, *-CH2-CH=CH2-CH2-*, and *-CH2-CH=CH2-CH2-*, are preferred, and alkenylene groups having 1 to 3 carbon atoms, such as *-CH=CH-* and *-CH=CH-CH2-*, are particularly preferred. However, the * in the above description indicates a bond. Examples of the alkynylene group include alkynylene groups having 1 to 10 carbon atoms such as *-C≡C-*, *-C≡C-CH2-*, *-CH2-C≡C-CH2-*, and *-CH2-CH2-C≡C-CH2-*. Of these, alkynylene groups having 1 to 6 carbon atoms such as *-C≡C-*, *-C≡C-CH2-*, and *-CH2-C≡C-CH2-* are preferred, and alkynylene groups having 1 to 3 carbon atoms such as *-C≡C-*, and *-C≡C-CH2-* are particularly preferred.
[0016] The anion represented by the general formula (1) may be used alone or in any combination and ratio of two or more. The content of the anion represented by the general formula (1) is not particularly limited and may be any as long as it does not significantly impair the effects of the present invention, but is usually 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and is usually 5 mass% or less, preferably 2 mass% or less, more preferably 1 mass% or less, based on the total amount of the non-aqueous electrolyte.
[0017] The ratio α / β of the content α of the anion represented by general formula (1) to the total content β of anions other than the anion represented by general formula (1) in the non-aqueous electrolyte is usually 0.0001 or more, preferably 0.0005 or more, more preferably 0.001 or more, and is usually 0.1 or less, preferably 0.05 or less, and more preferably 0.01 or less. By being within the above range, the positive electrode protection effect of the anion represented by general formula (1) is exerted, and side reactions in the battery are suppressed.
[0018] The anion represented by the above general formula (1) in the nonaqueous electrolyte and the nonaqueous electrolyte secondary battery is identified and its content is measured by magnetic resonance (NMR) spectroscopy.
[0019] The present invention also relates to a lithium salt having an anion represented by the above general formula (1). In the lithium salt having the anion represented by general formula (1), a suitable structure of the anion represented by general formula (1) is the same as the structure described above.
[0020] There is no particular limitation on the synthesis method of the lithium salt having the anion represented by the general formula (1). For example, the synthesis method in the embodiment where n is 4 includes a reaction between a hydroxy compound having a nitrile group and a tetrahydroborate anion. For example, the synthesis method in the embodiment where n is 3 includes a reaction between a tertiary borate compound and an alkoxide metal salt having a nitrile group. For example, the synthesis method in the embodiment where n is 2 includes a transesterification reaction between a tetraalkoxyborate anion and a hydroxy compound having a nitrile group.
[0021] [1-2. Electrolytes] <Lithium salt> As the electrolyte in the non-aqueous electrolytic solution, a lithium salt is usually used. In addition to two or more anions, the non-aqueous electrolyte contains cations. In the non-aqueous electrolyte, the largest component of the cations is Li. + It is preferable that: There are no particular limitations on the lithium salt, and any lithium salt may be used as long as it is known to be used for this purpose. Specific examples include the following: Examples include lithium fluoroborate, lithium fluorophosphate, lithium tungstate, lithium carboxylate, lithium sulfonate, lithium imide, lithium methide, lithium oxalate, and fluorine-containing organic lithium salts. Among them, the lithium fluoroborate salt is LiBF4; the lithium fluorophosphate salt is LiPF6, Li2PO3F, LiPO2F2; the lithium sulfonate salt is LiFSO3, CH3SO3Li; the lithium imide salt is LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide; and the lithium methide salt is LiFSO3, CH3SO3Li. , LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3; as lithium oxalate salts, lithium difluorooxalatoborate, lithium bis(oxalato)borate, lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalato)phosphate, lithium tris(oxalato)phosphate, etc. are more preferred because they have the effect of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, cycle characteristics, etc. More preferred are LiPF6, LiN(FSO2)2, lithium bis(oxalato)borate, and LiFSO3, and particularly preferred is LiPF6.
[0022] The non-aqueous electrolyte solution usually contains an anion constituting the above-mentioned lithium salt as an anion other than the anion represented by the general formula (1). Preferably, the non-aqueous electrolyte solution contains PF6 as an anion other than the anion represented by the general formula (1). - , BF4 - , ClO4 - , N(FSO2)2 - , N(FSO2)(CF3SO2) - , N(CF3SO2)2 - , N(C2F5SO2)2 - , difluorooxalatoborate, bisoxalatoborate, tetrafluorooxalatophosphate, difluorobisoxalatophosphate, and trisoxalatophosphate.
[0023] The electrolyte salts may be used alone or in combination of two or more. When two or more electrolytes are used and LiPF6 is used, it is preferable that the content of LiPF6 is the highest among the two or more electrolytes. In addition, in the non-aqueous electrolyte solution, the largest component of anions is PF6. - It is preferable that: The combination of two or more kinds of electrolyte salts is not particularly limited, but includes LiPF6 and LiN(FSO2)2; LiPF6 and LiBF4; LiPF6 and LiN(CF3SO2)2; LiBF4 and LiN(FSO2)2; LiBF4 and LiPF6 and LiN(FSO2)2. Among them, LiPF6 and LiN(FSO2)2; LiPF6 and LiBF4; LiBF4, LiPF6 and LiN(FSO2)2 are preferred.
[0024] The content of the electrolyte in the non-aqueous electrolyte solution (total content when two or more kinds are used) is not particularly limited, but is usually 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and is usually 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less, based on the total amount of the non-aqueous electrolyte solution. When the content of the electrolyte is within the above range, the electrical conductivity becomes appropriate for the battery operation, and therefore sufficient output characteristics tend to be obtained.
[0025] [1-3. Nonaqueous solvents] The non-aqueous electrolyte according to one embodiment of the present invention, like a general non-aqueous electrolyte, usually contains a non-aqueous solvent that dissolves the above-mentioned electrolyte as its main component. The non-aqueous solvent used is not particularly limited as long as it dissolves the above-mentioned electrolyte, and a known organic solvent can be used. Examples of the organic solvent include saturated cyclic carbonates, chain carbonates, chain carboxylates, cyclic carboxylates, ether compounds, sulfone compounds, and nitrile compounds (limited to those that do not have an anion represented by general formula (1)), but are not particularly limited thereto. The organic solvent can be used alone or in combination of two or more kinds. The combination of two or more organic solvents is not particularly limited, and examples thereof include saturated cyclic carbonates and chain carbonates, saturated cyclic carbonates and chain carboxylates, cyclic carboxylates or chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates. Among these, saturated cyclic carbonates and chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates are preferred.
[0026] [1-3-1. Saturated cyclic carbonates] Examples of saturated cyclic carbonates include those having an alkylene group having 2 to 4 carbon atoms, and from the viewpoint of improving battery characteristics resulting from an improvement in the degree of dissociation of lithium ions, saturated cyclic carbonates having 2 to 3 carbon atoms are preferably used. Specific examples of the saturated cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among them, ethylene carbonate or propylene carbonate is preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. The saturated cyclic carbonate may be used alone or in any combination and ratio of two or more. The content of the saturated cyclic carbonate is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but is usually 3% by volume or more, preferably 5% by volume or more, and is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. By setting the content of the saturated cyclic carbonate within this range, a decrease in electrical conductivity due to a decrease in the dielectric constant of the nonaqueous electrolyte can be avoided, and the large current discharge characteristics and cycle characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range, and the oxidation / reduction resistance of the nonaqueous electrolyte is improved, and the stability to the negative electrode and stability during high-temperature storage tend to be improved. In the present embodiment, the volume % refers to the volume at 25° C. and 1 atmospheric pressure.
[0027] [1-3-2. Chain carbonate] As the chain carbonate, for example, one having 3 to 7 carbon atoms is used, and in order to adjust the viscosity of the electrolyte solution within an appropriate range, a chain carbonate having 3 to 5 carbon atoms is preferably used. Specific examples of the chain carbonate include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate. Dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are particularly preferred. In addition, chain carbonates having fluorine atoms (hereinafter, sometimes abbreviated as "fluorinated chain carbonate") can also be suitably used. The number of fluorine atoms in the fluorinated chain carbonate is not particularly limited as long as it is 1 or more, but is usually 6 or less, and preferably 4 or less. When the fluorinated chain carbonate has multiple fluorine atoms, the multiple fluorine atoms may be bonded to the same carbon or different carbons. Examples of the fluorinated chain carbonate include fluorinated dimethyl carbonate derivatives such as fluoromethyl methyl carbonate; fluorinated ethyl methyl carbonate derivatives such as 2-fluoroethyl methyl carbonate; and fluorinated diethyl carbonate derivatives such as ethyl-(2-fluoroethyl) carbonate. The chain carbonate may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The amount of the chain carbonate is not particularly limited, but is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and usually 90% by volume or less, preferably 85% by volume or less, more preferably 80% by volume or less, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. By setting the amount of the chain carbonate in the above range, the viscosity of the nonaqueous electrolyte can be set in an appropriate range, the decrease in ion conductivity can be suppressed, and the output characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range. Furthermore, by combining a specific chain carbonate with ethylene carbonate in a specific content, the battery performance can be significantly improved. For example, when dimethyl carbonate and ethyl methyl carbonate are selected as specific chain carbonates, the content of ethylene carbonate is not particularly limited and is arbitrary as long as it does not significantly impair the effects of the present invention according to this embodiment, but it is usually 15% by volume or more, preferably 20% by volume or more, and usually 45% by volume or less, preferably 40% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, the content of dimethyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, the content of ethyl methyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution. By setting the content within the above range, there is a tendency for high temperature stability to be excellent and gas generation to be suppressed.
[0028] [1-3-3. Chain carboxylate esters] Examples of the chain carboxylate include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate. Among them, methyl acetate, ethyl acetate, propyl acetate, or butyl acetate is preferred from the viewpoint of improving battery characteristics. Chain carboxylates in which a portion of the hydrogen of the above-mentioned compounds is replaced with fluorine (e.g., methyl trifluoroacetate, ethyl trifluoroacetate, etc.) can also be used suitably. The content of the chain carboxylate is usually 1% by volume or more, preferably 5% by volume or more, more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. In this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily improved. In addition, the content of the chain carboxylate is usually 70% by volume or less, preferably 50% by volume or less, more preferably 40% by volume or less. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is in an appropriate range, the decrease in electrical conductivity is avoided, the increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily in a good range.
[0029] [1-3-4. Cyclic carboxylate esters] Examples of the cyclic carboxylate include γ-butyrolactone and γ-valerolactone. Among these, γ-butyrolactone is more preferable. Cyclic carboxylates in which some of the hydrogen atoms of the above-mentioned compounds are replaced with fluorine can also be used suitably. The content of the cyclic carboxylate is usually 1% by volume or more, preferably 5% by volume or more, more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. In this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily improved. In addition, the content of the cyclic carboxylate is usually 70% by volume or less, preferably 50% by volume or less, more preferably 40% by volume or less. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is in an appropriate range, the decrease in electrical conductivity is avoided, the increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily in a good range.
[0030] [1-3-5. Ether compounds] Preferred ether compounds include chain ethers having 3 to 10 carbon atoms, such as dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether, and cyclic ethers having 3 to 6 carbon atoms, such as tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxane, 2-methyl-1,3-dioxane, 4-methyl-1,3-dioxane, and 1,4-dioxane. Some of the hydrogen atoms in the above-mentioned ether compounds may be substituted with fluorine. Among these, as the chain ethers having 3 to 10 carbon atoms, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane are preferred because they have a high solvation ability for lithium ions, improve ionic dissociation, have low viscosity, and provide high ionic conductivity, and as the cyclic ethers having 3 to 6 carbon atoms, tetrahydrofuran, 1,3-dioxane, 1,4-dioxane, and the like are preferred because they provide high ionic conductivity. The content of the ether-based compound is not particularly limited, and may be any content as long as it does not significantly impair the effects of the present invention according to this embodiment. However, it is usually 1% by volume or more, preferably 2% by volume or more, more preferably 3% by volume or more, and usually 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less, based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. If the content of the ether-based compound is within the above range, it is easy to ensure the effect of improving the degree of lithium ion dissociation by the ether-based compound and improving the ion conductivity due to the decrease in viscosity of the non-aqueous electrolyte. In addition, when the negative electrode active material is a carbon-based material, the phenomenon in which the chain ether is co-inserted with the lithium ion can be suppressed, so that the input / output characteristics and the charge / discharge rate characteristics can be set to an appropriate range.
[0031] [1-3-6. Sulfone compounds] The sulfone compound is not particularly limited, and may be a cyclic sulfone or a chain sulfone. In the case of a cyclic sulfone, the carbon number is usually 3 to 6, preferably 3 to 5, and in the case of a chain sulfone, the carbon number is usually 2 to 6, preferably 2 to 5. In addition, the number of sulfonyl groups in one molecule of the sulfone compound is not particularly limited, but is usually 1 or 2. Examples of cyclic sulfones include monosulfone compounds such as trimethylene sulfones, tetramethylene sulfones, and hexamethylene sulfones, and disulfone compounds such as trimethylene disulfones, tetramethylene disulfones, and hexamethylene disulfones. Among these, from the viewpoint of dielectric constant and viscosity, tetramethylene sulfones, tetramethylene disulfones, hexamethylene sulfones, and hexamethylene disulfones are more preferred, and tetramethylene sulfones (sulfolanes) are particularly preferred. As the sulfolanes, sulfolane and sulfolane derivatives are preferred, and as the sulfolane derivatives, those in which one or more hydrogen atoms bonded to the carbon atoms constituting the sulfolane ring are substituted with a fluorine atom, an alkyl group, or a fluorine-substituted alkyl group are preferred. Among these, 2-methylsulfolane, 3-methylsulfolane, 2-fluorosulfolane, 3-fluorosulfolane, 2,3-difluorosulfolane, 2-trifluoromethylsulfolane, 3-trifluoromethylsulfolane, and the like are preferred because they have high ionic conductivity and high input / output. Examples of the chain sulfone include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, monofluoromethyl methyl sulfone, difluoromethyl methyl sulfone, trifluoromethyl methyl sulfone, pentafluoroethyl methyl sulfone, etc. Among these, dimethyl sulfone, ethyl methyl sulfone, or monofluoromethyl methyl sulfone is preferred in terms of improving the high-temperature storage stability of the electrolyte. The content of the sulfone-based compound is not particularly limited, and may be any as long as it does not significantly impair the effect of the present invention according to this embodiment, but is usually 0.3% by volume or more, preferably 0.5% by volume or more, more preferably 1% by volume or more, and is usually 40% by volume or less, preferably 35% by volume or less, more preferably 30% by volume or less, based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. If the content of the sulfone-based compound is within the above range, an electrolyte having excellent high-temperature storage stability tends to be obtained.
[0032] [1-3-7. Nitrile compounds] The nitrile compound does not have an anion represented by the general formula (1), and examples thereof include mononitriles having 2 to 10 carbon atoms, such as acetonitrile, propionitrile, butyronitrile, and valeronitrile, dinitriles having 4 to 12 carbon atoms, such as succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, and suberonitrile, and trinitriles, such as 1,3,6-hexanetricarbonitrile. A part of the hydrogen of the above-mentioned compound may be substituted with fluorine, and the molecule may have a carbon-carbon unsaturated bond. Among them, as the mononitrile, acetonitrile and propionitrile are preferred because they have low viscosity and improve ion conductivity, and as the dinitrile and trinitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, and 1,3,6-hexanetricarbonitrile are preferred from the viewpoint of high-temperature storage stability. The content of the nitrile compound is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but is usually 0.3% by volume or more, preferably 0.5% by volume or more, more preferably 1% by volume or more, and usually 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less, based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. If the content of the nitrile compound is within the above range, it is easy to obtain the effect of improving ion conductivity due to mononitrile, or the effect of improving high-temperature storage stability due to dinitrile and trinitrile.
[0033] [1-4. Auxiliaries] The non-aqueous electrolyte of the present invention may contain various auxiliary agents within the range that does not significantly impair the effects of the present invention. As the auxiliary agent, any conventionally known one may be used. In addition, the auxiliary agent may be used alone, or two or more kinds may be used in any combination and ratio. Examples of the auxiliary agent that may be contained in the non-aqueous electrolyte include cyclic carbonates having carbon-carbon unsaturated bonds, fluorine-containing cyclic carbonates, compounds having an isocyanate group, organic compounds having an isocyanuric acid skeleton, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having a cyano group (limited to those that do not have an anion represented by general formula (1)), silicon-containing compounds, aromatic compounds, non-fluorine-containing carboxylic acid esters, cyclic compounds having ether bonds, carboxylic acid anhydrides, borate anion-containing compounds, phosphate anion-containing compounds having P=O bonds and PF bonds, anion-containing compounds having S=O bonds, and oxalate complex anion-containing compounds. For example, compounds described in International Publication No. 2015 / 111676 can be mentioned. Among these, at least one anion-containing compound selected from a phosphate anion-containing compound having a PF bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound (hereinafter also referred to as a "specific anion-containing compound"), and / or at least one carbonate compound selected from a cyclic carbonate having a carbon-carbon unsaturated bond and a fluorine-containing cyclic carbonate (hereinafter also referred to as a "specific carbonate compound") is preferred. The content of the auxiliary is not particularly limited and may be any amount as long as it does not significantly impair the effects of the present invention; however, it is usually 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, and usually 10 mass% or less, preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 1 mass% or less, and particularly preferably less than 1 mass%, based on the total amount of the nonaqueous electrolyte solution. The cyclic compound having an ether bond can be used as an auxiliary in the non-aqueous electrolyte, and also includes those that can be used as a non-aqueous solvent as described in "1-3. Nonaqueous Solvent". When the cyclic compound having an ether bond is used as an auxiliary, it is used in an amount of less than 4 mass%. The borate anion-containing compound, the oxalate complex anion-containing compound, the monofluorophosphate anion-containing compound, and the difluorophosphate anion-containing compound can be used as an auxiliary in the non-aqueous electrolyte, and also includes those that can be used as an electrolyte as described in "1-2. Electrolyte". When these compounds are used as auxiliary, it is preferable to use them in an amount of 3 mass% or less.
[0034] [1-4-1. Specific anion-containing compounds] The specific anion-containing compound is usually an acid or a salt, and is preferably a salt, and the counter cation is preferably an alkali metal cation such as lithium, sodium, or potassium, and more preferably a lithium cation. At least one anion-containing compound selected from a phosphate anion-containing compound having a PF bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound can be used alone or in combination of two or more in any ratio. Among these, from the viewpoint of suppressing the amount of gas generated after high-temperature storage, a phosphate anion-containing compound having a PF bond and a P═O bond is preferred.
[0035] [1-4-1-1. Phosphate anion-containing compounds having PF bonds and P=O bonds] Examples of phosphate anion-containing compounds having an FP bond and a P=O bond include compounds containing a monofluorophosphate anion such as PO3F2-, and a difluorophosphate anion such as PO2F2-. Among these, compounds containing difluorophosphate anions are preferred from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface.
[0036] [1-4-1-2. Anion-containing compounds with S=O bonds] Examples of anion-containing compounds having an S=O bond include fluorosulfonate anions such as FSO3-; fluorosulfonylimide anions such as (FSO2)2N- and (FSO2)(CF3SO2)N-; compounds containing fluorosulfonylmethide anions such as (FSO2)3C-; and compounds containing alkylsulfate anions such as CH3SO4-. Among these, from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface, compounds containing a fluorosulfonate anion or a fluorosulfonylimide anion are preferred, and compounds containing a fluorosulfonate anion are more preferred.
[0037] [1-4-1-3. Compounds containing oxalate complex anions] The oxalate complex anion-containing compound is not particularly limited as long as it contains an anion having an oxalate complex in the molecule.The oxalate complex anion-containing compound is a compound containing an anion of an acid that forms a complex by coordinating or bonding with oxalic acid to a central atom, and can be exemplified by a compound containing a boron oxalate complex anion in which oxalic acid is coordinated or bonded to a boron atom, and a phosphorus oxalate complex anion in which oxalic acid is coordinated or bonded to a phosphorus atom. Examples of the boron oxalate complex anion include a bis(oxalate)borate anion and a difluorooxalateborate anion. Examples of the phosphorus oxalate complex anion include a tetrafluorooxalate phosphate anion, a difluorobis(oxalate)phosphate anion and a tris(oxalate)phosphate anion. Among these, from the viewpoint of forming a stable composite coating on the surface of the electrode, a compound containing a boron oxalate complex anion is preferred, and a compound containing a bis(oxalate)borate anion is more preferred.
[0038] (Content of specific anion-containing compounds) When the non-aqueous electrolyte solution contains a specific anion-containing compound, the content of the specific anion-containing compound (the total amount when two or more types are contained) in the total amount of the non-aqueous electrolyte solution is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.1 mass% or more, and is preferably 5 mass% or less, more preferably 4 mass% or less, even more preferably 3 mass% or less. If the content of the specific anion-containing compound is within the above range, the battery characteristics, particularly the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that the content of the specific anion-containing compound within the above mass ratio range can minimize the side reaction of the components of the non-aqueous electrolyte on the electrode surface. The identification and content of specific anion-containing compounds is determined by nuclear magnetic resonance (NMR) spectroscopy.
[0039] (Mass ratio of specific anion-containing compound to anion represented by general formula (1)) The mass ratio of the content of the specific anion-containing compound (total amount when two or more types are used) to the content of the anion represented by general formula (1) (specific anion-containing compound [g] / anion represented by general formula (1) [g]) is usually 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and is usually 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. When the mass ratio is within the above range, the battery characteristics, particularly the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that by containing the anion represented by general formula (1) and the specific anion-containing compound within the above mass ratio range, the side reaction of the components of the nonaqueous electrolyte on the electrode surface can be minimized.
[0040] (Mass ratio of specific anion-containing compound to electrolyte) When the non-aqueous electrolyte solution contains a specific anion-containing compound, the mass ratio of the content of the specific anion-containing compound (the total amount when there are two or more types) to the content of the electrolyte (specific anion-containing compound [g] / electrolyte [g]) is usually 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, still more preferably 0.025 or more, and is usually 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, still more preferably 0.35 or less. When the mass ratio is within the above range, the battery characteristics, particularly the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that by containing a specific anion-containing compound and an electrolyte within the above mass ratio range, the side reaction of the electrolyte in the battery system can be minimized.
[0041] [1-4-2. Specific carbonate compounds] The non-aqueous electrolyte preferably contains at least one carbonate compound selected from the group consisting of cyclic carbonates having carbon-carbon unsaturated bonds and cyclic carbonates having fluorine atoms. Among these, it is preferable to contain a cyclic carbonate having carbon-carbon unsaturated bonds, and it is more preferable to contain vinylene carbonate. These can be used alone or in combination of two or more in any ratio, and it is preferable to combine an unsaturated cyclic carbonate and a fluorinated cyclic carbonate, and it is more preferable to combine a vinylene carbonate and a fluorinated cyclic carbonate, and it is more preferable to combine an unsaturated cyclic carbonate and a monofluoroethylene carbonate, and it is even more preferable to combine vinylene carbonate and a monofluoroethylene carbonate.
[0042] (Content of specific carbonate compounds) The content of the specific carbonate compound (the total amount when two or more types are used) in the total amount of the nonaqueous electrolyte solution is usually 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, and even more preferably 0.5 mass% or more, and is usually 10 mass% or less, preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. If the content of the specific carbonate compound is within the above range, the battery characteristics, particularly the durability, can be improved. Although the reason for this is unclear, it is believed that the inclusion of the carbonate compound at this ratio forms a coating on the electrode, minimizing the side reaction of the components of the non-aqueous electrolyte. The identification and content of specific carbonate compounds is determined by nuclear magnetic resonance (NMR) spectroscopy.
[0043] (Mass ratio of specific carbonate compound to anion represented by general formula (1)) The mass ratio of the content of the specific carbonate compound (total amount when two or more kinds are used) to the content of the anion represented by the general formula (1) (specific carbonate compound [g] / anion [g] represented by the general formula (1)) is usually 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is usually 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. If the mass ratio is within the above range, the battery characteristics, especially durability, can be improved. The reason for this is unclear, but it is thought that by containing the specific carbonate compound within the above mass ratio range, a coating is formed on the electrode, and side reactions of the components of the non-aqueous electrolyte can be minimized.
[0044] (mass ratio of specific carbonate compound to electrolyte) In the non-aqueous electrolyte, the mass ratio of the content of the specific carbonate compound (total amount when two or more kinds are used) to the content of the electrolyte (specific carbonate compound [g] / electrolyte [g]) is usually 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, even more preferably 0.025 or more, and usually 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, even more preferably 0.35 or less. If the mass ratio is within the above range, the battery characteristics, especially durability, can be improved. The reason for this is unclear, but it is thought that by containing the carbonate compound and the electrolyte within the above mass ratio range, a coating is formed on the electrode, and the side reaction of the electrolyte in the battery system is minimized.
[0045] [1-4-2-1. Cyclic carbonates having carbon-carbon unsaturated bonds] The cyclic carbonate having a carbon-carbon unsaturated bond (hereinafter also referred to as "unsaturated cyclic carbonate") is not particularly limited as long as it is a cyclic carbonate having a carbon-carbon double bond or a carbon-carbon triple bond. Cyclic carbonates having an aromatic ring are also included in the unsaturated cyclic carbonate. Examples of the unsaturated cyclic carbonate include vinylene carbonates, ethylene carbonates substituted with a substituent having an aromatic ring, a carbon-carbon double bond or a carbon-carbon triple bond, phenyl carbonates, vinyl carbonates, allyl carbonates, catechol carbonates, etc. Among these, vinylene carbonates and ethylene carbonates substituted with a substituent having an aromatic ring, a carbon-carbon double bond or a carbon-carbon triple bond are preferred. Examples of vinylene carbonates include vinylene carbonate, methylvinylene carbonate, 4,5-dimethylvinylene carbonate, phenylvinylene carbonate, 4,5-diphenylvinylene carbonate, vinylvinylene carbonate, 4,5-vinylvinylene carbonate, allylvinylene carbonate, and 4,5-diallylvinylene carbonate. Examples of ethylene carbonates substituted with a substituent having an aromatic ring or a carbon-carbon double bond or a carbon-carbon triple bond include vinyl ethylene carbonate, 4,5-divinyl ethylene carbonate, 4-methyl-5-vinyl ethylene carbonate, 4-allyl-5-vinyl ethylene carbonate, ethynyl ethylene carbonate, 4,5-diethynyl ethylene carbonate, 4-methyl-5-ethynyl ethylene carbonate, 4-vinyl-5-ethynyl ethylene carbonate, 4-allyl-5-ethynyl ethylene carbonate, phenyl ethylene carbonate, 4,5-diphenyl ethylene carbonate, 4-phenyl-5-vinyl ethylene carbonate, 4-allyl-5-phenyl ethylene carbonate, allyl ethylene carbonate, 4,5-diallyl ethylene carbonate, and 4-methyl-5-allyl ethylene carbonate. Among these, vinylene carbonate, vinyl ethylene carbonate, and ethynyl ethylene carbonate are preferred since they form a more stable composite coating on the electrode, and one or more selected from vinylene carbonate and vinyl ethylene carbonate are more preferred, with vinylene carbonate being even more preferred. The unsaturated cyclic carbonates can be used alone or in combination of two or more kinds in any ratio.
[0046] [1-4-2-2. Cyclic carbonates containing fluorine atoms] The fluorine atom-containing cyclic carbonate is not particularly limited as long as it has a cyclic carbonate structure and contains a fluorine atom. Examples of cyclic carbonates having fluorine atoms include fluorinated cyclic carbonates having an alkylene group with 2 to 6 carbon atoms, and derivatives thereof, such as fluorinated ethylene carbonate (fluoroethylene carbonate) and derivatives thereof, and ethylene carbonate having a fluorine-containing group. Examples of derivatives of fluorinated ethylene carbonate include fluorinated ethylene carbonate substituted with an alkyl group (e.g., an alkyl group with 1 to 4 carbon atoms). Among these, fluoroethylene carbonate having 1 to 8 fluorine atoms and derivatives thereof are preferred. Examples of fluoroethylene carbonate and derivatives thereof having 1 to 8 fluorine atoms, as well as ethylene carbonate having a fluorine-containing group, include monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, and 4,4-difluoro-5,5-dimethylethylene carbonate. Among these, from the viewpoints of imparting high ionic conductivity to the electrolyte and facilitating the formation of a stable interface protective film, one or more selected from monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, and 4,5-difluoroethylene carbonate are preferred. The fluorine atom-containing cyclic carbonates can be used alone or in combination of two or more kinds in any ratio.
[0047] [2. Non-aqueous electrolyte secondary battery] A nonaqueous electrolyte secondary battery according to one embodiment of the present invention is a nonaqueous electrolyte secondary battery comprising a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, and a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and comprising a nonaqueous electrolyte.
[0048] [2-1. Non-aqueous electrolyte] As the non-aqueous electrolyte solution, the above-mentioned non-aqueous electrolyte solution is used. Note that, within the scope of the present invention, it is also possible to mix the above-mentioned non-aqueous electrolyte solution with other non-aqueous electrolyte solutions.
[0049] [2-2. Positive electrode] The positive electrode has a positive electrode active material on at least a portion of the surface of a current collector.
[0050] [2-2-1. Positive electrode active material] The positive electrode active material (lithium transition metal compound) used in the positive electrode will be described below.
[0051] [2-2-1-1. Lithium transition metal compounds] The lithium transition metal compound is a compound having a structure capable of desorbing and inserting lithium ions, and examples thereof include sulfides, phosphate compounds, silicate compounds, borate compounds, lithium transition metal composite oxides, etc. Among these, phosphate compounds and lithium transition metal composite oxides are preferred, and lithium transition metal composite oxides are more preferred. Examples of the lithium transition metal composite oxide include those having a spinel structure or olivine structure that enable three-dimensional diffusion of lithium ions, and those having a layered structure that enables two-dimensional diffusion of lithium ions. Among these, lithium transition metal composite oxides having a layered structure are preferred from the viewpoint of improving the battery capacity.
[0052] A lithium transition metal composite oxide having a spinel structure is generally represented by the following composition formula (1). Li x’ M' y’ O4···(1) (In formula (1), x' is 0.8≦x'≦1.5 and 1.9≦y'≦2.1, and M' contains at least one transition metal element.) Specifically, LiMn2O4, LiCoMnO4, LiNi 0.5 Mn 1.5 O4, LiCoVO4, etc.
[0053] A lithium transition metal composite oxide having an olivine structure is generally represented by the following composition formula (2). Li x” M” y” PO4···(2) (In formula (2), x″ is 0.8≦x″≦1.5, 0.9≦y″≦1.1, and M″ contains at least one transition metal element.) Specifically, LiFePO4 and the like can be mentioned.
[0054] A lithium transition metal composite oxide having a layered structure is generally represented by the following composition formula (3). Li 1+x M y O2···(3) (In formula (3), x is −0.2≦x≦0.5, 0.9≦y≦1.1, and M contains at least one transition metal element.) Specifically, LiCoO2, LiNiO2, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, Li 1.0 Ni 0.70 Co 0.15 Mn 0.15 Examples include O2. Among these, a lithium transition metal composite oxide having a layered structure represented by the following composition formula (4) is more preferable. Li a1 Ni b1 M c1 O2···(4) (In formula (4), a1, b1, and c1 are numerical values that satisfy 0.80≦a1≦1.10, 0.30≦b1≦0.98, and 0.01≦c1≦0.5, respectively, and satisfy 0.9≦b1+c1≦1.1. M contains at least one element selected from the group consisting of Co, Mn, Al, Mg, Zr, Fe, Ti, and Er.) In particular, from the viewpoint of the structural stability of the lithium transition metal composite oxide, a transition metal oxide represented by the following composition formula (5) is preferable. Li a2 Ni b2 Co c2 M d2 O2···(5) (In formula (4), a2, b2, c2, and d2 are numerical values that satisfy 0.80≦a2≦1.10, 0.50≦b2≦0.98, 0.01≦c2<0.50, and 0.01≦d2≦0.50, respectively, and satisfy 0.9≦b2+c2+d2≦1.1. M contains at least one element selected from the group consisting of Mn, Al, Mg, Zr, Fe, Ti, and Er.) In the composition formula (5), M preferably contains Mn or Al, and more preferably contains Mn. This is because the structural stability of the lithium transition metal oxide is increased and structural deterioration during repeated charging and discharging is suppressed. Specifically, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15Al 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.50 Co 0.20 Mn 0.30 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, Li 1.0 Ni 0.70 Co 0.15 Mn 0.15 O2, etc.
[0055] [2-2-1-2. Introduction of different elements] Furthermore, elements (foreign elements) other than the elements contained in the above composition formula may be incorporated into the lithium transition metal composite oxide.
[0056] [2-2-1-3. Surface coating] The positive electrode active material may have a surface-attached substance having a different composition from the positive electrode active material. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate. These surface-adhering substances can be attached to the surface of the positive electrode active material, for example, by dissolving or suspending them in a solvent, adding them to the positive electrode active material by impregnation, and drying them. The amount of the surface-attaching substance is preferably 1 μmol / g or more, and more preferably 10 μmol / g or more, and is usually 1 mmol / g or less, relative to the positive electrode active material. In this specification, a positive electrode active material having the above-mentioned surface-adhering substance attached to the surface thereof is also referred to as a "positive electrode active material".
[0057] [2-2-1-4. Blend] These positive electrode active materials may be used alone or in any combination of two or more in any ratio.
[0058] [2-2-2. Positive electrode composition and manufacturing method] The configuration and manufacturing method of the positive electrode are described below. In this embodiment, the positive electrode using the positive electrode active material can be manufactured by a conventional method. That is, the positive electrode active material and the binder, and if necessary, the conductive material and the thickener, etc. are mixed in a dry state to form a sheet, which is then pressed onto the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium such as an aqueous solvent or an organic solvent to form a slurry, which is then applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode. In addition, for example, the above-mentioned positive electrode active material may be roll-formed into a sheet electrode, or may be compression-formed into a pellet electrode. Hereinafter, the case where the slurry is successively applied to the positive electrode current collector and then dried will be described.
[0059] [2-2-2-1. Active material content] The content of the positive electrode active material in the positive electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.
[0060] [2-2-2-2.Conductive materials] Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; and carbon-based materials such as amorphous carbon such as needle coke. The conductive material may be used alone or in any combination and ratio of two or more. The conductive material is used so that it is usually contained in the positive electrode active material layer in an amount of 0.01% by mass or more and 50% by mass or less.
[0061] [2-2-2-3. Binder] The binder used in producing the positive electrode active material layer is not particularly limited as long as it is a material that is dissolved or dispersed in a liquid medium for a slurry, for example, when the positive electrode active material layer is formed by a coating method. In view of weather resistance, chemical resistance, heat resistance, flame retardancy, and the like, preferred are fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene; and CN group-containing polymers such as polyacrylonitrile and polyvinylidene cyanide. In addition, mixtures, modified products, derivatives, random copolymers, alternating copolymers, graft copolymers, block copolymers, etc. of the above polymers can also be used. The binder may be used alone or in any combination and ratio of two or more kinds. When a resin is used as a binder, the weight average molecular weight of the resin is optional as long as it does not significantly impair the effects of the present invention, but is usually at least 10,000, preferably at least 50,000, and particularly preferably at least 100,000, and is usually at most 3,000,000, preferably at most 950,000, and particularly preferably at most 900,000. If the molecular weight is within this range, the strength of the electrode is improved, and the electrode can be suitably formed. The proportion of the binder in the positive electrode active material layer is usually 0.1% by mass or more and 80% by mass or less.
[0062] [2-2-2-4. Current collector] The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum. Among them, aluminum is preferable. The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. Among these, metal foil or metal thin film is preferable. The metal thin film may be appropriately formed into a mesh shape. When the positive electrode current collector has a plate or film shape, the thickness of the current collector is not limited. It is greater than 1 μm and less than 1 mm.
[0063] [2-2-2-5. Thickness of positive electrode plate] The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the positive electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the positive electrode plate is usually 10 μm or more and 500 μm or less on one side of the current collector.
[0064] [2-2-2-6. Electrode density] The positive electrode active material layer obtained by coating and drying is preferably compressed by a hand press, a roller press, or the like in order to increase the packing density of the positive electrode active material. The density of the positive electrode active material layer present on the current collector is usually 1.5 g / cm 3 More than 4.5g / cm 3 The following is the result.
[0065] [2-2-2-7. Surface coating of positive electrode plate] In addition, the positive electrode plate may have a substance having a different composition from that of the positive electrode plate attached to its surface, and the substance in question may be the same as the surface-attached substance that may be attached to the surface of the positive electrode active material.
[0066] [2-3. Negative electrode] The negative electrode has a negative electrode active material on at least a portion of the surface of a current collector.
[0067] [2-3-1. Negative electrode active material] The negative electrode active material used in the negative electrode is not particularly limited as long as it can electrochemically absorb and release metal ions. Specific examples include carbon-based materials, materials containing metal elements and / or metalloid elements that can be alloyed with Li, lithium-containing metal composite oxide materials, and mixtures thereof. Among these, it is preferable to use carbon-based materials, materials containing metal elements and / or metalloid elements that can be alloyed with Li, and mixtures of materials containing metal elements and / or metalloid elements that can be alloyed with Li and carbon-based materials, in terms of good cycle characteristics and safety, and excellent continuous charging characteristics. These may be used alone or in any combination of two or more.
[0068] [2-3-1-1. Carbon-based materials] Examples of carbonaceous materials include natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Of these, natural graphite is preferred. The carbonaceous materials may be used alone or in any combination and ratio of two or more. Examples of natural graphite include scaly graphite, scaly graphite, and / or graphite particles obtained by subjecting such graphite to treatment such as spheroidization or densification. Among these, from the viewpoint of particle packing property or charge / discharge rate characteristics, spherical or ellipsoidal graphite particles that have been subjected to spheroidization treatment are particularly preferred. The average particle size (d50) of the graphite particles is usually 1 μm or more and 100 μm or less.
[0069] [2-3-1-2. Properties of carbon-based materials] The carbonaceous material as the negative electrode active material preferably satisfies at least one of the characteristics such as the physical properties and shape shown in the following (1) to (4), and particularly preferably satisfies several of them at the same time. (1) X-ray diffraction parameters The d value (interlayer distance) of the lattice plane (002 plane) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 0.335 nm to 0.360 nm. Also, the crystallite size (Lc) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 1.0 nm or more. (2) Volume-based average particle size The volume-based average particle size of a carbon-based material is the volume-based average particle size (median diameter) determined by a laser diffraction / scattering method, and is usually 1 μm or more and 100 μm or less. (3) Raman R value, Raman half-width The Raman R value of a carbon-based material is a value measured using argon ion laser Raman spectroscopy, and is usually 0.01 or more and 1.5 or less. In addition, the 1580 cm -1 The Raman half-width in the vicinity is not particularly limited, but is usually 10 cm -1 More than 100cm -1 The following is the result. (4) BET specific surface area The BET specific surface area of a carbon-based material is the value of the specific surface area measured using the BET method, and is usually 0.1 m 2 ·g -1 More than 100m 2 ·g -1 The following is the result. The negative electrode active material may contain two or more carbon-based materials with different properties. Here, the properties refer to X-ray diffraction parameters, volume-based average particle size, Raman R value, Raman half-width, and BET specific surface area. Preferred examples include the case where the volume-based particle size distribution is not symmetric about the median diameter, the case of containing two or more carbon-based materials with different Raman R values, and the case of containing two or more carbon-based materials with different X-ray parameters, etc.
[0070] [2-3-1-3. Material containing a metal element and / or a metalloid element capable of alloying with Li] As the material containing a metal element and / or a metalloid element capable of alloying with Li, any conventionally known material can be used. However, from the viewpoints of capacity and cycle life, for example, it is preferably a single substance or a compound of a metal and / or a metalloid element that may be coated with carbon and is selected from the group consisting of Sb, Si, Sn, Al, As, and Zn. Further, when the material containing a metal element and / or a metalloid element capable of alloying with Li contains two or more elements, the material may be an alloy material composed of an alloy of these metals. In addition, examples of the material containing a metal element and / or a metalloid element capable of alloying with Li include oxides, nitrides, carbides, etc. These may contain two or more metal elements and / or metalloid elements capable of alloying with Li. Among them, metal Si (hereinafter, may be referred to as Si) or a Si-containing inorganic compound is preferable in terms of achieving a high capacity. In addition, the material containing a metal element and / or a metalloid element capable of alloying with Li may already be alloyed with Li during the production of the negative electrode described later. In this specification, Si or a Si-containing inorganic compound is collectively referred to as a Si compound. Specific examples of the Si compound include SiO x (0≦x≦2), etc. Specific examples of the metal compound alloyed with Li include Li y Si(0<y≦4.4), Li2SiO 2+z (0<z≦2), etc. As the Si compound, a Si oxide (SiO x1When 0 < x1 ≤ 2), it is preferable in terms of having a larger theoretical capacity compared to graphite, or amorphous Si or nano-sized Si crystals are preferable in that alkali ions such as lithium ions can easily enter and exit, enabling high capacity to be obtained. When the material containing a metal element and / or a metalloid element capable of alloying with Li is in the form of particles, its average particle diameter (d50) is usually 0.01 μm or more and 10 μm or less from the viewpoint of cycle life.
[0071] [2-3-1-4. Mixture of particles of a material containing a metal element and / or a metalloid element capable of alloying with Li and graphite particles] The mixture of particles of a material containing a metal element and / or a metalloid element capable of alloying with Li and graphite particles used as the negative electrode active material may be a mixture in which the particles of the material containing a metal element and / or a metalloid element capable of alloying with Li and the graphite particles described above are mixed in a state of particles of independent materials, or may be a composite in which the particles of the material containing a metal element and / or a metalloid element capable of alloying with Li are present on the surface or inside of the graphite particles. The content ratio of the particles of the material containing a metal element and / or a metalloid element capable of alloying with Li to the total of the particles of the material containing a metal element and / or a metalloid element capable of alloying with Li and graphite particles is usually 1 mass% or more and 99 mass% or less.
[0072] [2-3-1-5. Lithium-containing metal composite oxide material] The lithium-containing metal composite oxide material used as the negative electrode active material is not particularly limited as long as it can occlude and release lithium ions, but a lithium-containing metal composite oxide material containing titanium is preferable from the viewpoint of high current density charge and discharge characteristics, and a composite oxide of lithium and titanium (hereinafter, may be abbreviated as "lithium titanium composite oxide") is more preferable, and a lithium titanium composite oxide having a spinel structure is particularly preferable because it greatly reduces the output resistance. Also, lithium and / or titanium of the lithium titanium composite oxide may be substituted with at least one element selected from the group consisting of other metal elements such as Al, Ga, Cu, and Zn. Lithium titanium composite oxide, Li 4 / 3 Ti 5 / 3 O4, Li1Ti2O4 and Li 4 / 5 Ti 11 / 5 O4 is preferred. In addition, examples of lithium titanium composite oxides in which part of lithium and / or titanium is replaced with other elements include Li 4 / 3 Ti 4 / 3 Al 1 / 3 O4 is preferred.
[0073] [2-3-2. Negative electrode composition and manufacturing method] The negative electrode may be produced by any known method as long as it does not significantly impair the effects of the present invention. For example, the negative electrode may be produced by adding a binder, a liquid medium such as an aqueous solvent or an organic solvent, and if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, which is applied to a current collector, dried, and then pressed to form a negative electrode active material layer.
[0074] [2-3-2-1. Active material content] The content of the negative electrode active material in the negative electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.
[0075] [2-3-2-2. Electrode density] The negative electrode active material layer obtained by coating and drying is preferably compacted by hand press, roller press, etc. to increase the packing density of the negative electrode active material. There are no particular restrictions on the electrode structure when the negative electrode active material is made into an electrode, but the density of the negative electrode active material layer present on the current collector is usually 1 g cm -3 More than 2.2g cm -3 The following is the result.
[0076] [2-3-2-3. Thickener] The thickener is usually used to adjust the viscosity of the slurry. The thickener is not particularly limited, but specifically includes carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, and sodium salts thereof. These may be used alone or in any combination and ratio of two or more. When a thickener is used, the ratio of the thickener to the negative electrode active material is usually 0.1 mass % or more and 5 mass % or less.
[0077] [2-3-2-4. Binder] There are no particular limitations on the binder that binds the negative electrode active material, so long as it is a material that is stable in the nonaqueous electrolyte solution and the liquid medium used in the production of the electrode. Specific examples include rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, and tetrafluoroethylene-ethylene copolymers. These may be used alone or in any combination and ratio of two or more. The ratio of the binder to the negative electrode active material is usually 0.1% by mass or more and 20% by mass or less. In particular, when the binder contains a rubber-like polymer such as SBR as a main component, the ratio of the binder to the negative electrode active material is preferably 0.1% by mass or more and 5% by mass or less. Also, when the binder contains a fluorine-based polymer such as polyvinylidene fluoride as a main component, the ratio of the binder to the negative electrode active material is preferably 1% by mass or more and 15% by mass or less.
[0078] [2-3-2-5. Current collector] Any known current collector can be used to hold the negative electrode active material. Examples of the current collector for the negative electrode include metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel, and copper is particularly preferred from the standpoints of ease of processing and cost. The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. Among these, metal foil or metal thin film is preferable. The metal foil and metal thin film may be appropriately formed into a mesh shape. When the negative electrode current collector has a plate or film shape, the current collector may have any thickness, but it is usually 1 μm or more and 1 mm or less.
[0079] [2-3-2-6. Thickness of negative electrode plate] The thickness of the negative electrode (also called "negative electrode plate") is designed to match the positive electrode used and is not particularly limited, but the thickness of the negative electrode active material layer, calculated by subtracting the thickness of the current collector from the thickness of the negative electrode material, is usually 15 μm or more and 300 μm or less.
[0080] [2-3-2-7. Surface coating of negative electrode plate] The negative electrode plate may have a surface to which a substance having a different composition from the negative electrode active material (surface-attached substance) is attached. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.
[0081] [2-4. Separator] A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuiting. In this case, the non-aqueous electrolyte is usually impregnated into the separator before use. There are no particular limitations on the material and shape of the separator, and any known material can be used as long as it does not significantly impair the effects of the present invention.
[0082] [2-5.Battery design] [2-5-1. Electrode group] The electrode group may be either a laminated structure of the positive electrode plate and the negative electrode plate with the separator interposed therebetween, or a structure of the positive electrode plate and the negative electrode plate wound in a spiral shape with the separator interposed therebetween. The ratio of the volume of the electrode group to the internal volume of the battery is usually 40% or more and 90% or less.
[0083] [2-5-2. Current collection structure] In the case where the electrode group has the above-mentioned laminated structure, a structure in which the metal core parts of the electrode layers are bundled and welded to a terminal is preferably used. A structure in which multiple terminals are provided in the electrode to reduce resistance is also preferably used. In the case where the electrode group has the above-mentioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and the negative electrode and bundling them to a terminal.
[0084] [2-5-3.Protection elements] The protective element may be a PTC (Positive Temperature Coefficient) element whose resistance increases with heat generation due to excessive current, a thermal fuse, a thermistor, a valve (current cutoff valve) that cuts off the current flowing through the circuit due to a sudden increase in the battery's internal pressure or temperature during abnormal heat generation, etc. It is preferable to select the above protective element so that it will not operate under normal use at high current, and it is even more preferable to design it so that abnormal heat generation or thermal runaway does not occur even without the protective element.
[0085] [2-5-4. Exterior body] A non-aqueous electrolyte secondary battery is usually constructed by housing the above-mentioned non-aqueous electrolyte, negative electrode, positive electrode, separator, etc. in an exterior body (exterior case). There are no limitations on this exterior body, and any known exterior body can be used as long as it does not significantly impair the effects of the present invention. The material of the exterior case is not particularly limited as long as it is a substance that is stable to the non-aqueous electrolyte solution used, but from the viewpoint of weight reduction, metal such as aluminum or an aluminum alloy, or a laminate film is preferably used. Examples of exterior cases using the above metals include those in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed, airtight structure, and those in which the above metals are used with a resin gasket in between to form a crimped structure.
[0086] [2-5-5. Shape] The shape of the exterior case is also arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Compound 1 used in Example 1 and Compound 2 used in Comparative Example 1 are shown below.
[0088] compound 1 [ka]
[0089] compound 2 [ka]
[0090] <Synthesis of Compound 1> Compound 1 was synthesized by the following method.
[0091] <Synthesis Example> The analytical methods used in the following synthesis examples are as follows. [Nuclear magnetic resonance (NMR) analysis] 1 H-NMR was measured at 400 MHz using a Bruker 400 Ultrashield. Samples were dissolved in deuterated dimethyl sulfoxide ((CD3)2SO) and measured.
[0092] <Synthesis Example 1> Compound 1: Synthesis of lithium tetrakis(2-cyanoethoxy)borate 2-Cyanoethanol (7.11 g, 0.100 mmol) was dissolved in tetrahydrofuran (25 mL), and a tetrahydrofuran solution of lithium tetrahydroborate (4 M, 5.00 mL) was added dropwise over 1 hour while stirring under ice cooling. After stirring at room temperature for 1.5 hours, the mixture was stirred under reflux until no more foaming occurred. The precipitated solid was collected by filtration, washed with tetrahydrofuran and acetonitrile, and dried under reduced pressure to obtain lithium tetrakis(2-cyanoethoxy)borate. 1 H-NMR(400MHz,(CD3)2SO):δ=3.45(br,8H),2.48(t,8H)
[0093] <Synthesis of compound 2> Compound 2 was synthesized as Sample 2 described in JP-A-2016-533624.
[0094] [Preparation of positive electrode] The positive electrode active material was lithium nickel cobalt manganese composite oxide (Li 1.0 Ni 0.70 Co 0.15 Mn 0.15 90 parts by mass of O2), 7 parts by mass of acetylene black as a conductive material, and 3 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone solvent with a disperser to form a slurry. This was evenly applied to both sides of a 15 μm thick aluminum foil, dried, and pressed to form a positive electrode.
[0095] [Preparation of negative electrode] 98 parts by mass of natural graphite was mixed with 1 part by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed in a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil having a thickness of 10 μm, dried, and pressed to form a negative electrode.
[0096] [Preparation of non-aqueous electrolyte] A reference electrolyte was prepared by dissolving thoroughly dried LiPF6 as an electrolyte at 1.0 mol / L (12.2 mass%; concentration in the non-aqueous electrolyte) in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) (volume ratio of EC:DMC:EMC = 3:4:3) under a dry argon atmosphere.
[0097] [Example 1] A non-aqueous electrolyte solution was prepared by adding compound 1 to the total amount of the reference electrolyte solution so that the amount was 0.1 mass%. - The ratio α / β to the anion content (β mass %) was 0.008.
[0098] [Comparative Example 1] The reference electrolyte was used as it was to prepare a non-aqueous electrolyte solution.
[0099] [Comparative Example 2] A non-aqueous electrolyte solution was prepared in the same manner as in Example 1, except that Compound 1 was replaced with Compound 2.
[0100] [Manufacture of non-aqueous electrolyte secondary batteries] The above positive electrode, negative electrode, and polyethylene separator were laminated in the order of negative electrode, separator, and positive electrode to prepare a battery element. This battery element was inserted into a bag made of a laminate film of aluminum (thickness 40 μm) coated on both sides with a resin layer so that the positive and negative electrode terminals were protruding, and the above prepared nonaqueous electrolyte solution was then poured into the bag and vacuum sealed to prepare a laminate type nonaqueous electrolyte secondary battery.
[0101] <Evaluation of non-aqueous electrolyte secondary batteries> [Initial conditioning] In a thermostatic bath at 25°C, the non-aqueous electrolyte secondary battery prepared by the above method was charged at a constant current of 0.025C (1C means a current value required for charging or discharging for 1 hour. The same applies below.) to 3.6V, then constant current-constant voltage charging (hereinafter referred to as CC-CV charging) was performed at 0.17C to 4.2V, and then discharged at 0.17C to 2.5V. The discharge capacity at this time was designated as "initial discharge capacity". Table 3 below shows the value of the initial discharge capacity when the initial discharge capacity of Comparative Example 1 is taken as 100. Next, constant current-constant voltage charging was performed at 0.17C to 4.1V. Then, the battery was held at 60°C for 24 hours to perform aging. After that, the battery was discharged at 0.17C to 2.5V, and then CC-CV charged at 0.17C to 4.2V, after which it was discharged at 0.2C to 2.5V and charged at 0.17C to 3.7V for initial conditioning.
[0102] [High temperature storage test] The non-aqueous electrolyte secondary battery after the initial conditioning was again subjected to CC-CV charging at 0.17C to 4.3V, and then stored at high temperature at 60°C for one week. After that, the non-aqueous electrolyte secondary battery was sufficiently cooled, and then discharged at 0.17C to 2.5V. The capacity at this time during discharge was taken as the "residual capacity after high temperature storage". Table 1 below shows the value of the residual capacity after high temperature storage when the residual capacity after high temperature storage of Comparative Example 1 is taken as 100.
[0103] [Table 1]
[0104] From Table 1, it can be seen that Example 1, which used a nonaqueous electrolyte solution containing an anion represented by general formula (1), has a superior initial discharge capacity and a superior remaining capacity after high-temperature charged storage compared to Comparative Example 1, which used standard electrolyte solution 1 as is, and Comparative Example 2, which used an electrolyte solution containing compound 2. The above effects are believed to be due to the formation of a protective layer on the positive electrode surface by compound 1, which suppresses side reactions within the battery.
Claims
1. A non-aqueous electrolyte solution containing a non-aqueous solvent and two or more kinds of anions, at least one of which contains an anion represented by general formula (1): 【Chemistry 6】 (In general formula (1), X is a divalent hydrocarbon group, R is a hydrocarbon group, and n is an integer of 2 or more and 4 or less.)
2. 3. The nonaqueous electrolyte solution according to claim 1, wherein α / β is 0.0001 or more and 0.1 or less, where α is the content (mass%) of the anion represented by general formula (1) and β is the total content (mass%) of anions other than the anion represented by general formula (1).
3. The non-aqueous electrolyte contains PF as an anion other than the anion represented by general formula (1). 6 - , B.F. 4 - , ClO 4 - , N(FSO 2 ) 2 - , N(FSO 2 ) (CF 3 SO 2 ) - , N(CF 3 SO 2 ) 2 - , N(C 2 F 5 SO 2 ) 2 - 3. The non-aqueous electrolyte solution according to claim 1, further comprising at least one selected from the group consisting of tetrafluorooxalatophosphate, difluorobisoxalatophosphate, difluorooxalatophosphate, and trisoxalatophosphate.
4. 3. The nonaqueous electrolyte solution according to claim 1, wherein the nonaqueous solvent is at least one selected from the group consisting of saturated cyclic carbonates, chain carbonates, chain carboxylates, cyclic carboxylates, sulfone-based compounds, ether-based compounds, and nitrile-based compounds (limited to those not having an anion represented by general formula (1)).
5. A nonaqueous electrolyte secondary battery comprising the nonaqueous electrolyte according to claim 1 or 2.
6. A lithium salt having an anion represented by general formula (1): 【Chemistry 7】 (In general formula (1), X is a divalent hydrocarbon group, R is a hydrocarbon group, and n is an integer of 2 or more and 4 or less.)
Citation Information
Patent Citations
Use of reactive lithium alkoxylates as electrolyte additives in electrolytes for lithium-ion batteries
JP2016533624A